Neuromuscular taping reduced pain intensity after the eccentric activity in senior high school students - Septyaningrum Putri Purwoto; Adi Pranoto; Fajar Hidayatullah; Khoirul Anwar; Heni Yuli Handayani; Haryo Mukti Widodo; Fajar Hamdhan Utama; Agus Himawan; Muhammad Zainal Arifin; Tri Setyo Utami (Sport TK)
Neuromuscular taping is one method that can be used to reduce the impact of pain after eccentric activity. The purpose of this study was to determine the effect of neuromuscular taping on the pain intensity after eccentric activity. This was an experimental study with the design of a randomized post-test control group. The 14 samples obtained were then randomly divided into two groups. Neuromuscular taping treatment (NMT) was used before performing eccentric activities. The eccentric activity performed was shoulder flexion-elbow extension. After 24 hours of recovery, the pain intensity was measured using a visual analog scale. The results of the Mann Whitney u test showed that there was no significant difference in pain intensity (p ≥ 0.05). The conclusion of this study was that the neuromuscular taping after eccentric activity did not reduce the pain intensity after 24 hours of recovery. However, there was a tendency that the neuromuscular taping treatment group showed lower pain intensity so NMT decreased the pain intensity after eccentric activity.